2001
DOI: 10.1177/104063870101300606
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Virulent Rhodococcus Equi in Soil from Five R. Equi-Endemic Horse-Breeding Farms and Restriction Fragment Length Polymorphisms of Virulence Plasmids in Isolates from Soil and Infected Foals in Texas

Abstract: Abstract. Rhodococcus equi isolates (462) obtained from 64 soil samples collected on 5 R. equi-endemic horse-breeding farms and isolates from 100 infected foals in Texas were examined to determine the prevalence and genotypic diversity of virulence-associated plasmids. Isolates were tested for the presence of 15-17-kDa virulence-associated protein antigens (VapA) by immunoblotting and virulence-associated plasmids by PCR. Plasmid DNAs were isolated and analyzed by digestion with restriction endonucleases for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
60
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(64 citation statements)
references
References 20 publications
2
60
0
2
Order By: Relevance
“…Most clinical isolates from the Americas, Australia, and Europe contain 85-kb type I or 87-kb type I plasmids. The 85-kb type II plasmid is found only in French isolates and the 85-kb type III and type IV plasmids only in isolates from Texas [12,16,27]. These five types of virulence plasmids have never been isolated from Japanese samples.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most clinical isolates from the Americas, Australia, and Europe contain 85-kb type I or 87-kb type I plasmids. The 85-kb type II plasmid is found only in French isolates and the 85-kb type III and type IV plasmids only in isolates from Texas [12,16,27]. These five types of virulence plasmids have never been isolated from Japanese samples.…”
Section: Discussionmentioning
confidence: 99%
“…1B). The digestion patterns were then compared with 10 representative virulence plasmid types (85-kb types I, II, III, and IV; 87-kb types I and II; and 90-kb types I, II, III, and IV), which have already been reported [16,22,27,31]. As shown in Fig.…”
Section: Isolation Of R Equi From Soil and Fecal Samples From Nativementioning
confidence: 99%
See 1 more Smart Citation
“…However, avirulent R. equi, which have no virulence-associated antigens or plasmids and do not cause disease in foals, are distributed widely in horses and their environments [10,23]. Epidemiological studies have revealed that horse-breeding farms with endemic infections are heavily contaminated with virulent R. equi [9,17].The restriction-enzyme digestion patterns of virulent virulence plasmids from foals have allowed the plasmids of virulent isolates to be categorized into 12 closely related types and have revealed geographic differences in the distributions of these virulence plasmids, not only throughout the world, but also within Japan [7,11,15,16,19,20,22]. In a recent study, we isolated virulent R. equi containing the 90-kb type II plasmid that has been found in isolates from the native Kiso horses of Japan, from fecal and environmental samples of the native Jeju horse and thoroughbred horse farms on Jeju Island, Korea, and a new variant, the 90-kb type V plasmid [20].…”
mentioning
confidence: 99%
“…The restriction-enzyme digestion patterns of virulent virulence plasmids from foals have allowed the plasmids of virulent isolates to be categorized into 12 closely related types and have revealed geographic differences in the distributions of these virulence plasmids, not only throughout the world, but also within Japan [7,11,15,16,19,20,22]. In a recent study, we isolated virulent R. equi containing the 90-kb type II plasmid that has been found in isolates from the native Kiso horses of Japan, from fecal and environmental samples of the native Jeju horse and thoroughbred horse farms on Jeju Island, Korea, and a new variant, the 90-kb type V plasmid [20].…”
mentioning
confidence: 99%